2023
DOI: 10.1021/acscatal.3c00973
|View full text |Cite
|
Sign up to set email alerts
|

Deoxygenative Silylation of C(sp3)–O Bonds with Hydrosilane by Cooperative Catalysis of Gold Nanoparticles and Solid Acids

Abstract: Efficient deoxygenative silylation of C(sp3)–O bonds with hydrosilanes by supported Au catalysts is described. Gold nanoparticles supported on TiO2 enabled various hydrosilanes to be used as sources of silyl groups in C–Si cross-coupling reactions. A variety of alkyl acetates and propargyl carbonates participated in the Au-catalyzed reactions to furnish the corresponding alkyl and allenylsilanes in high yields. In addition, Au/TiO2 was also effective for ring-opening silylation of cyclic ethers. A detailed mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…The present Au-catalyzed borylation could access alkyl boronates with short alkyl chains ( 3b) or bulky substituents at the α-position of a C–B bond ( 3c and 3k ) for which few examples have been reported so far in catalytic borylation. As we reported previously, the present Au/ZrO 2 catalyst is effective for the silylation of C­(sp 3 )–O bonds . In the reaction of primary alkyl acetates under the optimized reaction conditions, C–O bond silylation preferentially proceeded to give alkylsilane, thus providing the target alkyl boronates in reduced yields.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…The present Au-catalyzed borylation could access alkyl boronates with short alkyl chains ( 3b) or bulky substituents at the α-position of a C–B bond ( 3c and 3k ) for which few examples have been reported so far in catalytic borylation. As we reported previously, the present Au/ZrO 2 catalyst is effective for the silylation of C­(sp 3 )–O bonds . In the reaction of primary alkyl acetates under the optimized reaction conditions, C–O bond silylation preferentially proceeded to give alkylsilane, thus providing the target alkyl boronates in reduced yields.…”
supporting
confidence: 57%
“…Thus, the development of a universal method that would enable the conversion of widespread C­(sp 3 )–O bonds to C­(sp 3 )–B bonds is still a significant challenge. Recently, we demonstrated that the combination of supported Au catalysts and disilane promoted the homolysis of stable C­(sp 3 )–O bonds of alkyl acetates to generate alkyl radicals (Scheme D) . In that reaction, single-electron transfer from disilane to Au nanoparticles (NPs) and subsequent fragmentation of Si–Si bonds generated silyl radicals.…”
mentioning
confidence: 99%
“…Our previous study revealed that metal oxidesupported Au catalysts promoted silylation of CÀ O bonds by using disilanes or hydrosilanes as silyl sources. [45,46] Furthermore, we proposed that the reacton initiated by the SET oxidation of silyl compounds promoted by Au(I) species at the interface of Au NPs and metal oxide supports. However, as shown in Figure 1, there is few amounts of Au(I) species on the surface of Au/C before the reaction.…”
Section: Mechanistic Investigationmentioning
confidence: 99%
“…[34][35][36][37][38][39][40][41][42][43][44] Recently, we found that homolytic cleavage of a stable C(sp 3 )À O bond took place in the presence of a supported Au NPs catalyst, which realized radical alkyl-silyl cross-coupling to give alkylsilanes (Scheme 1). [45,46] Singleelectron oxidation of disilane triggered the fragmentation of a SiÀ Si bond to furnish highly reactive silyl radicals, [47] implying that supported Au NPs function as heterogeneous single-electron transfer catalysts without light irradiation. Against this background, we envisaged that supported Au NPs catalysts could promote radical cross-coupling via single-electron transfer from disilanes to redox-active esters such as N-hydroxy phthalimide (NHPI) ester.…”
Section: Introductionmentioning
confidence: 99%
“…This selectively catalysed hydrogenation of aromatic compounds with the same size as the template molecules. In addition, combining metal nanoparticles with appropriate supports realises a synergistic catalysis that e ciently promotes the desired reaction while enhancing the stability of the active species [5][6][7][8] . Aromatic compounds are a ubiquitous building block in various elds, and many efforts have been made to establish methodologies for their synthesis.…”
Section: Introductionmentioning
confidence: 99%